Manajemen Makna Terkoordinasi Pada Proses Komunikasi Interpersonal Dalam Bimbingan Skripsi Prodi Ilmu Komunikasi - Pranawukir, Iswahyu; Sukma, Agus Hitopa; Misnan, Misnan; Alamsyah, Alamsyah; Putri, Erita Riski (Expose: Jurnal Ilmu Komunikasi, 2024)
The research purpose is to explore the of thesis guidance meaning management in communication studies programs that combined with interpersonal strategies, and to unite the interrelationships between the interpersonal communication process and the coordination of meaning management. The research method is qualitative method with a constructivist paradigm with a case study research method. The research was conducted on three campuses in Jakarta: Mpu Tantular University, Surya University and IBI Kosgoro 1957. The results showed that interpersonal communication strategies in a thesis guidance managed by interpersonal relationship approaches. It formed coordination of meaning through: openness, empathy, positiviness, supportiveness, and equality.